PO58 Drug interaction between curcuma and the antidepressant fluoxetine on behavioral despair and biochemical markers of kidney and liver function in Wistar rats - Trujillo De Los Santos, Jennifer; Cueto Escobedo, Jonathan; Rodríguez Landa, Juan Francisco; Guillén Ruiz, Gabriel; Limón Vázquez, Ana Karen; Rivadeneyra Domínguez, Eduardo; Valenzuela Limón, Olga Lidia (Revista Productos Naturales, 2025)
Depression affects more than 300 million people worldwide, and its treatment includes SSRIs, but they have a prolonged latency. Research suggests that curcuma could be a therapeutic alternative. In this study, the interactions between curcuma and fluoxetine were evaluated. The results showed that curcuma, both individually and in combination with subthreshold doses of fluoxetine, had antidepressant effects without altering renal and hepatic function. However, in effective combinations, it cancels out the effect, which is related to a pharmacological interaction. These findings suggest that curcuma could be a natural option for treating depression.
Keywords: fluoxetine; curcuma; antidepressants; food supplement